2022
DOI: 10.3390/pr10061225
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of an Industrial β-Glucosidase from Aspergillus fumigatus and Its Use for Cellobiose Hydrolysis

Abstract: In this study, several covalent methods of immobilization based on acrylic supports, Schiff bases and epoxides have been applied to a commercial cocktail with a high β-glucosidase activity secreted by Aspergillus fumigatus. This cocktail was preliminary compared to a commercial secretome of Aspergillus niger, which was also subjected to the aforementioned immobilization methods. Due to its higher activity, the cocktail from A. fumigatus immobilized on ReliZyme™ HA403 activated with glutaraldehyde was employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Several protocols for immobilization via CLEAs [24][25][26][27] and on solid supports via multiple binding [28][29][30][31][32][33] have been reported. Covalent immobilization by a multi-point attachment was realized, for example, by using supports that expose epoxy groups [28,34,35] or functionalized amine groups with glutaraldehyde [36][37][38][39], bisepoxides [28,35], or other difunctional reagents [40]. Site-specific immobilization enables targeted immobilization and can avoid detrimental binding (e.g., if the catalytic site is facing the surface), excessive enzyme rigidification, and unspecific interactions (e.g., with active site amino acids).…”
Section: Introductionmentioning
confidence: 99%
“…Several protocols for immobilization via CLEAs [24][25][26][27] and on solid supports via multiple binding [28][29][30][31][32][33] have been reported. Covalent immobilization by a multi-point attachment was realized, for example, by using supports that expose epoxy groups [28,34,35] or functionalized amine groups with glutaraldehyde [36][37][38][39], bisepoxides [28,35], or other difunctional reagents [40]. Site-specific immobilization enables targeted immobilization and can avoid detrimental binding (e.g., if the catalytic site is facing the surface), excessive enzyme rigidification, and unspecific interactions (e.g., with active site amino acids).…”
Section: Introductionmentioning
confidence: 99%
“…To test the goodness of the proposed kinetic model, some statistical parameters were provided by the software: root main squared error (RMSE) (Equation ( 1)) measures the cumulative error between the experimental data and the fitted model, so it should tend to zero. This parameter is based on the sum of squared residuals (SSR), represented in Equation (2), that indicates the overall error present in the model, in respect of experimental data [19,36].…”
Section: Mathematical Methodsmentioning
confidence: 99%
“…The release of glucose by β-glucosidases is vital because glucose is a treasure trove of energy and a crucial building block for the synthesis of biofuels. It has been demonstrated that immobilizing β-glucosidases on appropriate substrates enhances their catalytic activity, which may have consequences for a range of industrial uses, such as the generation of biofuel [41], [42], [43].…”
Section: Endoglucanases and Exoglucanasesmentioning
confidence: 99%